Rocuronium, Long Last Forever? - Portela, Inês; Jacob, Miguel; Monteiro, Catarina; Silva, Paula; Lares, Ana (Journal of the Portuguese Society of Anesthesiology, 2019)
It is known there is a wide variability in duration of action of nondepolarizing muscle relaxants which contributes to the considerable incidence of residual neuromuscular blockade and its multiple deleterious consequences for the patient. We report a case of an elderly otherwise healthy male patient with an unusually long-lasting neuromuscular blockade during laparoscopic surgery, illustrating the relevance of objective neuromuscular monitoring in an adequate and safe patient recovery and discussing factors that can potentiate rocuronium bromide duration of action.